Linguocognitology & Systemology: Integrativity in actu (Theoretical and Methodological Aspects of Interaction) - D. M. Mironova (Дискурс, 2022)
Introduction. The study analyzes the systemological adequacy of the cognitive approach to language and on this basis suggests a method of cognitive-systemological interpretation of linguistic facts. The cognitive approach is in a good agreement with the functional nature of the object of linguistics. At the same time the theoretical and methodological guidelines of cognitive linguistics allow us to reveal more deeply and holistically the ontological properties of language as a system phenomenon.Methodology and sources. The research tasks involve assessing the role and novelty of cognitive linguistics in description language as a system, in substantiating the significance of interpreting thought-language interaction in the context of certain parameters of the system nature of language and, as a consequence, in developing a possible method of such interpretation. The paper used the axiomatic-deductive method, as well as the descriptive method with its techniques of observation, generalization, systematization and interpretation. In addition, at the stage of presenting the method, we resorted to the modeling its procedure. The research material consists of the methodological principles of cognitive linguistics, philosophical dialectics and general theory of systems presented in domestic and foreign sources.Results and discussion. The analysis of the methodology and subject area of linguocognitology suggests that cognitive models of language have the great explanatory power and completeness in terms of representing this phenomenon as a naturally developing complex and large open-type system. In this sense, linguocognitology appears as a logical continuation of the development of a system approach in linguistics at a new level. The work proposes a structural and logical organization of the method of cognitive- systemological interpretation in the form of a number of procedures.Conclusion. As a result of the conducted searches, the author comes to the conclusion about the practicability of cognitive-systemological interpretation of multilevel phenomena of semantic space, which is due, on the one hand, to the close links of natural language with the cognitive environment and, on the other hand, its system-wide nature. The systemological aspect of the consideration on the cognitive essence of language corresponds both to the ontology of the object itself and to the value orientations of the philosophy of science and the modern paradigm of linguistics. The research aspect, emphasizing the cognitive causality of system parameters or the systemological status of linguistic facts, underlies the identification of two versions of this method.